A Cross-Sectional Study of Speech in 10-Year-Old Children with Cleft Palate: Results and Issues of Rater Reliability - Brunnegård, Karin; Lohmander, Anette (The Cleft palate-craniofacial journal, 2007)
Objectives: To describe speech based on perceptual evaluation in a group of 10-year-old children with cleft palate. A secondary aim was to investigate the reliability of speech-language pathologists’ perceptual assessment of cleft palate speech. Design: Retrospective cross-sectional study in children with cleft palate. External raters made assessments from randomized speech recordings. Subjects: Thirty-eight children with unilateral cleft lip and palate (UCLP) or cleft palate only (CPO) and 10 children in a comparison group. Main Outcome Measures: Ratings of hypernasality, hyponasality, audible nasal air leakage, weak pressure consonants, and articulation. Exact agreement and weighted kappa values were used for reliability. Results: Hypernasality was found in 25% of children with a cleft of the soft palate (CSP), 33% of children with a cleft of the hard and soft palate (CHSP), and 67% of children with a UCLP. Similar results were found for audible nasal air leakage. Articulation errors were found in 6% of the CHSP group and 25% of the UCLP group, whereas no child in the CSP group had articulation errors. The reliability was moderate to good for different variables, with lowest values for hypernasality. Conclusions: Speech results in this series seem less satisfactory than those reported in other published international studies, but it is difficult to draw any certain conclusions about speech results because of large methodological differences. Further developments to ensure high reliability of perceptual ratings of speech are called for.